2021
DOI: 10.3389/fpsyt.2021.744898
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Distinct Fractional Amplitude of Low-Frequency Fluctuation Patterns in Major Depressive Disorders With and Without Gastrointestinal Symptoms

Abstract: Objective: Gastrointestinal (GI) symptoms are fairly common somatic symptoms in depressed patients. The purpose of this study was to explore the influence of concomitant GI symptoms on the fractional amplitude of low-frequency fluctuation (fALFF) patterns in patients with major depressive disorder (MDD) and investigate the connection between aberrant fALFF and clinical characteristics.Methods: This study included 35 MDD patients with GI symptoms (GI-MDD patients), 17 MDD patients without GI symptoms (nGI-MDD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
3
1
Order By: Relevance
“…Particularly, the SFG had been found to play a vital role in bipolar disorder with increased fALFF values because the superior frontal gyrus might be a key region related with perceived stress and further cognitive and emotional control [ 46 ]. Nevertheless, different from our outcomes that the abnormally ascending fALFF values of the SFG correlated with the scores of clinical anxiety scales, patients of major depressive disorder with gastrointestinal symptoms presented more severe depressive symptoms with an increased fALFF in the right SFG [ 47 ]. Hence, we hypothesized the dysfunction of the SFG might imply the potential tendency of translating the anxiety into depression in the observed patients of CP/CPPS.…”
Section: Discussioncontrasting
confidence: 83%
“…Particularly, the SFG had been found to play a vital role in bipolar disorder with increased fALFF values because the superior frontal gyrus might be a key region related with perceived stress and further cognitive and emotional control [ 46 ]. Nevertheless, different from our outcomes that the abnormally ascending fALFF values of the SFG correlated with the scores of clinical anxiety scales, patients of major depressive disorder with gastrointestinal symptoms presented more severe depressive symptoms with an increased fALFF in the right SFG [ 47 ]. Hence, we hypothesized the dysfunction of the SFG might imply the potential tendency of translating the anxiety into depression in the observed patients of CP/CPPS.…”
Section: Discussioncontrasting
confidence: 83%
“…Insomniacs are often accompanied by depression. Studies have also found the abnormally spontaneous neural activity in the middle frontal gyrus in patients with depression (Fu et al, 2021). In addition to abnormal brain function, the decrease of gray matter volume in the frontal lobe was also found in insomniacs with impaired attention executive function (Joo et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…The MFG is one part of the dlPFC and is closely correlated with eudemonic well-being [ 96 ]. Many studies have revealed that structural or functional abnormalities in the SFG and MFG are common in MDD patients [ 97 101 ]. In addition, MDD patients with anhedonia exhibited decreased regional homogeneity in SFG [ 102 ].…”
Section: Discussionmentioning
confidence: 99%